Travel Behavior during the 2021 British Columbia Floods Using De-identified Network Mobility Data - Enqi Liao; Syeda N. Zehra; Stephen D. Wong (Findings)
This study investigates residents’ emergent travel behavior before, during, and after the 2021 British Columbia Floods. Using de-identified network mobility data, we analyze travel patterns centered around the municipality of Hope in British Columbia, Canada. Our findings reveal significant drops in travel during the peak of the floods, corresponding with major transportation infrastructure failure. The slow recovery process and dispersed residents highlight the insufficient resilience of key transportation corridors. Furthermore, the results underscore the importance of network mobility data being: 1) privacy-protected, 2) efficient and easy to examine, and 3) adaptable.